OPTIMALIZATION ON GAS POWER PLANT USING COGENERATION/TRIGENERATION CYCLE - Ajeng R, Candrika
Economic growth in various sectors which offset by the increase in population resulted in an increased need for energy, especially electricity. In order to obtain the electricity need, the development of new infrastucture for power plant and optimalization the existing power generation facilities also required in order to manage the efficiency and performance. Cogeneration cycle is one of a scheme of power and heat generation by utilizing gas as a fuel which has not been utilize in optimal way in Indonesia. This study discuss in detail the optimization of energy at power plant with Cogeneration scheme by modifiy the existing scheme with recently developt Trigeneration scheme. This study explore the potential way to utilize the energy that generated by the Trigeneration system, evaluate the economic and long-term viability if the modification is done to the existing Cogeneration system and becoming Trigeneration system. Power and Utility Plant owned by PT PI Energi insed the area of PT Petrokimia Gresik, built to meet the demand for electricity and steam for PT Petrokimia Gresik (PKG) which is currently developing a new fertilizer production facility, Amurea II Plant. Simulation of the simple cycle Power plant obtain efficiency of gas turbine around 26.49% meanwhile with addition of Cogeneration Cycle to the system obtain the efficiency higher in 80.59%. Result show that modification Cogeneration to Trigeneration System obtain total thermal efficiency to 81.12% and produce cooling fluid with load approximately 0.4391 MW along with cooling of 124.87 tonne/h water.